Synthetic biology education and pedagogy: a review of evolving practices in a growing discipline - Menard, Jyler; Diep, Patrick; Sheikh, Fatima; Escobar, Andres; Dykstra, Christien B.; Sajtovich, Victoria A.; Ahmadi, Atiyeh; Bodyreva, Elena; Boucinha, Austin; Chandrasekharan, Saranya; Duan, Jin; Emond, Christian; et al. (Frontiers in Education, 2024)
Synthetic biology is a growing field with an increasing number of successful applications. Yet, synthetic biology (SynBio) education initiatives are underreported and disconnected from each other. In this review we survey the literature on SynBio education and stratify this body of work into three categories: classroom activities, course designs, and program-level curricula-planning. For each category, we discuss the methods used to assess students' experiences and achievement of learning objectives. Throughout, we identify trends and opportunities for further development in SynBio education. We determined that the design of low-cost education kits is a growing opportunity to support student learning at the level of classroom activities. In support of that work, we present a mapping of published education kits onto Bloom's taxonomy, taking into account increasing accumulation of knowledge through continued experience. We further found that project-based learning is used widely and has proven effective in course designs. To facilitate such activities, we provide a high-level guide for the conversion of a didactic course into a project-based learning course. Further, we note that, currently, programs are delivered primarily at the graduate level, taking inspiration from traditional degree programs while incorporating interdisciplinary training. Finally, we find that design-based research may provide an effective framework for an iterative, mixed-method study design. To support such efforts, we provide a schematic overview of design-based research and its application to a learning progression for interdisciplinary skills. We conclude with a discussion of specific learning concepts that may be useful to SynBio educators and education researchers.